Public employment services and vulnerable youth in the EU: The case of rural NEETs - Simões, F. (2024)
The Covid‐19 pandemic created unprecedented pressure to accelerate public employment services (PES) digitalisation across Europe. In fact, there is now a considerable amount of funding dedicated to that goal in broadband policy packages, such as the Recovery and Resilience Mechanism. This pressure for digitalizing PES presumes that its benefits outweigh the existing risks, regardless of citizens’ singularities, such as vulnerable young people going through the school‐to‐work transition. Bearing that in mind, and following a bioecological model framework, our article addresses two main goals. Firstly, based on a targeted literature review, we detail the challenges and possibilities posed by PES digitalisation for vulnerable young people in EU countries, which have been widely overlooked in the literature. We specifically argue that despite several practical advantages (e.g., releasing staff from time‐consuming administrative tasks), PES digitalisation will only be beneficial for vulnerable young people if three interrelated challenges are taken into account: nurturing trust in institutions and digital tools, supporting digital transformation of PES institutional organization, and adopting a co‐design lens for PES digitalisation. Secondly, using a knowledge integration approach, we describe a model for assessing PES capacity to digitally support rural young people not in employment, education, or training to enter the labour market. We conclude that the overemphasis on the expected advances of overall PES digitalisation must be followed by thoughtful consideration of PES digitalisation processes to ensure EU social inclusion targets for the younger generations.